In-silico analysis of Thr767Ile pathogenic variant in the MSH6 gene in family with endometrial cancer. (July 2019) - Stembalska, Agnieszka; Klapecki, Jakub; Pławski, Andrzej; Karpinski, Paweł
Abstract: Objective: To examine the mechanism of pathogenity of Thr767Ile variant on MSH6 protein. Study design: We describe a family diagnosed with endometrial cancer in two generations associated with variant in the MSH6 gene (p. Thr767Ile / c. 2300C>T) (rs587781462). MSH6 c. 2300C>T was associated with autosomal-dominant pattern of inheritance. MSH6 c. 2300C>T has pathogenic status in ClinVar and LOVD3 databases but it has never been described in context of hereditary endometrial cancer. We utilized a number of in-silico bioinformatic approaches using MSH6 protein sequence and structural information to assess influence of Thr767Ile on MSH6 properties. Results: MSH6 Thr767 is highly conservative amino acid among various kingdoms of organisms. Thr767Ile was predicted deleterious and likely decreases affinity of MSH2-MSH6 complex to DNA but not affect interaction between MSH2 and MSH6. Conclusions: To the best of our knowledge, this is the first description of MSH6 T767I pathogenic variant that could be associated with a hereditary endometrial cancer. Bioinformatic analyses showed that T767I substitution most likely affects the MSH6 most important role, which is a DNA binding.